CHILDREN’S MAP READING ABILITIES IN RELATION TO DISTANCE PERCEPTION, TRAVEL TIME AND LANDSCAPE - Aikaterini APOSTOLOPOULOU; Aikaterini KLONARI (European Journal of Geography)
Children’s cognition of distance is influenced by functional distance and estimations of travel time which increases with the presence of natura l or artificial barriers. In this paper we investigate pupil’s associations of landscape and travel time in a map reading task of equal distance target cities. More than 330 11 year old pupils atte nding the fifth grade from 18 public primary schools located in city and rural areas participated in a research with the use of a 3D relief map of central Greece for deci sion making activities relating travel time to geomorphologic barriers. We hypothe sized that pupils from city areas would design straight line routes regardless of the physical landscape influenced by the linear and rectangular outlines of city environments in opposition to pupils living in rural areas that would design curved routes according to the landscape. The results indicate that children relate landforms with travel time by identifying physical obstacles on the map. Pupils that selected the city of destination correctly justified their answers by identifying geomorpho logic features on the map. However, the performance of urban pupils outpaces rural pupils’ performance postulating that the quality and quantity of edu cational resources in ci ty areas may influence positively spatial cognition.